Implementasi Foot Massage Untuk Mengontrol Tekanan Darah Pada Lansia Dengan Hipertensi - Hirza Ainin Nur (Pusat Riset dan Inovasi Nasional, 2024)
The elderly or elderly will experience health problems called aging process. The problem that often occurs in the elderly is hypertension. Hypertension is a condition in which the systolic blood pressure is more than 140 mmHg and/or diastolic is more than 90 mmHg. Risk factors that affect hypertension are lifestyle, stress and psychology, environmental factors and age. Management in patients with hypertension can be done pharmacologically and non-pharmacologically, among others, by using foot massage therapy. The purpose of this case study is to determine the evaluation of the application of foot massage to control blood pressure in the elderly with hypertension. This type of case study research is with an evaluation method of nursing care process approach. The sample number was 2 respondents, namely the elderly suffering from mild-moderate hypertension. Foot massage therapy is carried out every two days according to part-time taking medication for 7 times within 2 weeks with a duration of 20 minutes. Blood pressure measurement is measured before and after the procedure using observation sheet instruments, SOPs, tools to measure blood pressure, namely aneroid sphygmomanometers, stethoscopes, and booklets to record results. The results found that respondent 1, the first day's blood pressure results of 160/100 mmHg (moderate hypertension) dropped to 130/80 mmHg (abnormally high) on day 7. Then, in respondent 2 the results of the first day's blood pressure of 150/100 mmHg (mild hypertension) dropped to 130/80 mmHg (abnormally high) on day 7. It can be concluded, that the application of foot massage can control blood pressure in the elderly with hypertension.